Simulation and visualization of spraying droplets behavior and deposition within virtual rice canopy - Ding, Weilong; Zhu, Fenglong; Jin, Mengjie; Xu, Lifeng; Zhang, Yuping (International Journal of Agricultural and Biological Engineering, 2022)
Models for accurately simulating pesticide droplet deposition and transmission mechanism in rice canopies can provide an effective and economic tool to optimize methods for spraying pesticides, adjuvant formulation, and spray parameters. However, the current studies on the modeling of spray droplet deposition within rice plants are still very limited. Aiming at this problem, a method to model and visualize spray transmission and deposition within the canopy of rice plants was proposed. Firstly, a particle system was used to simulate the spraying scene of droplets. Then an improved method to determine the behavior of rebound and shatter of the droplets in the virtual scene was proposed. The deposition of spraying droplets on a leaf was calculated according to the inclination angles of the leaf, the characteristics of the leaf surface, and the physical and spatial characteristics of the droplets. The experiment shows that the method can simulate the behavior of the spraying droplets within a virtual scene of a rice plant, which may provide a reference for the study of spray deposition in the canopy of the crop.Keywords: virtual rice plant, droplet deposition, behavior simulation, spray sceneDOI: 10.25165/j.ijabe.20221505.7099Citation: Ding W L, Zhu F L, Jin M J, Xu L F, Zhang Y P. Simulation and visualization of spraying droplets behavior and deposition within virtual rice canopy. Int J Agric & Biol Eng, 2022; 15(5): 19–27.